Nature and nurture poverty and environment in Asia and the Pacific. - sian Development Bank (ADB Avenue, Mandaluyong City Asian Development Bank, 2009)
Overcoming environmental degradation is necessary if we are to reduce poverty. This is especially true in Asia and the Pacific, where two thirds of the world's poor live. Environmental degradation in the region is pervasive and it is accelerating. This publication provides an overview of poverty-environment interactions and presents some of these case studies and others that show how poor communities in Asia and the Pacific have sought to break out of poverty through local actions that improved their environment or made them less vulnerable to environmental stress."--Publisher website.
Chapter 1. Introduction. -- Chapter 2. Sustaining Natural Resources and Reducing Poverty. -- Chapter 3. Improving Urban Environmental Quality and Reducing Poverty. -- Chapter 4. Reducing the Environmental Vulnerability of the Poor. -- Chapter 5. Lessons. -- Chapter 6. Looking Ahead.
"Publication stock no. ARM090171"--T.p. verso.
Includes bibliographical references.
Keywords: Poverty -- Asia; Poverty -- Pacific Area; Environmental degradation -- Asia; Environmental management -- Asia -- ase studies